Shape memory alloy engineering : for aerospace, structural and biomedical applications. - Concilio, Antonio, 1964-; Antonucci, Vincenza; Auricchio, Ferdinando; Lecce, Leonardo; Sacco, Elio, 1955- (Butterworth-Heinemann, 2021)
Shape Memory Alloy Engineering: For Aerospace, Structural and Biomedical Applications, Second Edition embraces new advancements in materials, systems and applications introduced since the first edition. Readers will gain an understanding of the intrinsic properties of SMAs and their characteristic state diagrams. Sections address modeling and design process aspects, explore recent applications, and discuss research activities aimed at making new devices for innovative implementations. The book discusses both the potential of these fascinating materials, their limitations in everyday life, and tactics on how to overcome some limitations in order to achieve proper design of useful SMA mechanisms.